The Role of Islamic Banking in Supporting the Halal Community through MSMEs - Soritua Ahmad Ramdani Harahap; Sulthon El Hasbi Rambe; Ahmad Iqbal (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: MSMEs have a role in maintaining economic stability, especially in Indonesia. Understanding of Islamic principles needs to be supported from all parties, one of which is with BSI Banking which always encourages and works together in advancing MSMEs in Indonesia. However, there are still several aspects that still need to be optimized such as understanding sharia, halal certificates and others to create a halal ecosystem in Indonesia. This research uses qualitative research methods. The results of this study indicate that the five Islamic principles starting from tawhid, balance, free will, responsibility and ihsan must always be maintained. With the role of Bank Syariah Indonesia, it will be an extraordinary driving force for MSME / business actors in advancing their products while still paying attention to Islamic values. Keywords: MSMEs, Bank Syariah Indonesia, Islamic principles.